Pengembangan dan Kemajuan Desa Wisata terhadap Peningkatan Pendapatan Masyarakat Lokal di Desa Gagah, Kabupaten Pamekasan - Anggraeni, Dyah; Angraini, Merie Satya; Asy’ari, Muhammad Asim (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This research aims to determine the influence of the development and progress of Tourism Villages on the Income of the Local Community of Gagah Village, Kadur District, Pamekasan Regency, and what impacts this has on the community's economy. Gallant Village is a tourist village that has abundant village potential which has become a tourist village business entity. This research method uses descriptive quantitative methods. Based on research results, village development has an effect on community income. This is shown by the increase in the level of development of tourist villages, the impact on community income. Village progress influences community income. This is shown by the more developed tourist villages that will affect people's income.